Influence Of Problem Based Learning Models (Pbl) To Problem-Solving Ability Mathematical - Irwan, Irwan (Riviera Publishing, 2022)
The problem of this research is the low ability of understanding mathematical concept student grade VIII. The purpose of this research is to determine if there is influence of model Problem Based Learning (PBL) to ability of understanding mathematical concept student grade VIII. The type of the research is a quasi-experimental research, with pretest-posttest control group design. This population is student of grade VIII MTs Swasta Al-Muttaqiin i, while the sample is consists of two classes that the total is 20 to each other. The data in this research used t test. Average test conceptual understanding ability of mathematical before and after learning there is an increase. From the t test analysis, obtained result that tcount greater that ttable so that Ha received and H0 refused, it means there is a significance influence between model Problem Based Learning (PBL) and conceptual understanding ability of mathematical student. Learning by using model Problem Based Learning (PBL) is the one alternative in increasing conceptual understanding ability of mathematical student. Therefore can be concluded that there is an influence of model Problem Based Learning (PBL) to ability of understanding mathematical concept student grade VIII.